The Endings of Early Medieval Kingdoms: Murder or Natural Causes? - Escalona, Julio (Reti Medievali Rivista, 2016)
This short text presents reflections drawn from the essays collected in this special issue as well as from the debates of the Salamanca symposium where they originated. It does not purport to represent the authors’ ideas beyond what is strictly necessary for my argument. Firstly, I make a critical review of how political collapse is addressed in the different contributions, within a comparative perspective. Secondly, I suggest some theoretical approaches than can contribute to develop a comparative perspective on the endings of the early medieval kingdoms, based upon the notions of complexity, scale and agency.